'It had to be done': genetic testing decisions for arrhythmogenic right ventricular cardiomyopathy. (28th October 2014) - Etchegary, H.; Pullman, D.; Simmonds, C.; Young, T.‐L.; Hodgkinson, K.
<x xml:space="preserve">Abstract</x> Arrhythmogenic right ventricular cardiomyopathy (ARVC) is a heritable disease of the heart muscle, causing life‐threatening ventricular arrhythmias, sudden cardiac death and/or biventricular heart failure. Little research examines ARVC genetic test decisions, despite the gravity of the condition. This qualitative study used semi‐structured interviews to explore the testing decisions of 21 individuals across 15 families segregating a well‐studied, particularly lethal form of ARVC caused by a p.S358L TMEM43 mutation. Genetic testing decisions were rarely described as 'decisions' per se, but rather 'something that had to be done'. This perception was attributed to personality type or personal suspicion of carrying the TMEM43 mutation, but most often was described in the context of testing for other family members, usually children. Participants related a strong need to rule out risk, more for children than for themselves, but lingering doubts remained about personal and children's risk for ARVC, even when gene test results were negative. Study findings highlight the interdependent nature of genetic test decisions and suggest that an individualistic conception of autonomy in genetic services may not meet the needs of affected families. Findings also suggest the need for follow‐up support of families affected by ARVC, including for those individuals testing negative for the family mutation.